PSYCHOLINGUISTIC PREREQUISITES FOR DEVELOPING LISTENING COMPETENCE OF PRE-SERVICE TEACHERS THROUGH FICTION AUDIOBOOKS - Iryna Bilianska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The quality of the professional training of foreign language teachers presupposes high level of their listening competence. However, in non-authentic language environment developing proficiency in listening is recognized as a difficult task. Therefore, Ukrainian methodologists are in search of new ways to improve listening skills of pre-service teachers. The purpose of this article is to explore recent research into psycho-linguistic issues and analyse the grounds for the development of listening competence by means of fiction audiobooks. This paper therefore deals with the analysis of cognitive processes and psychological mechanisms, listening stages (motivational, analytically-synthetic, executive and controlling). It goes on to focus on artistic perception and its mechanisms and the information processing mechanisms. Since fiction is an art of words, specific features of listening to audiobooks are primarily related to the category of art. It is revealed that at all levels of the structure of an artistic text (genre, plot, structure) there are some authors guidelines which guide, direct attention and activate apperception. The typical benchmarks of audiobooks that help to activate apperception (genre, cover, title, sample, summary, reviews, author / narrator, volume, rating etc.) have been determined. It has been found that listening to an audiobook should result into its "projection" in the recipients mind. The "projection" may be materialized through a secondary text. It is concluded that the mechanisms of listening to fiction audiobooks are: 1) mental processes (perception, thinking, memory, attention); 2) psychological mechanisms (speech hearing, articulation, anticipation, comprehension, working memory); 3) mechanisms of artistic perception (emotions and feelings, imagination, apperception, figurative and associative thinking); 4) information processing mechanisms (mechanism of equivalent replacements, transcoding, compression, expansion, transformation). Thus, the following prerequisites for developing listening competence of future teachers have been singled out: 1) interests of students, motivating factors should be considered; 2) students must be taught to analyze, synthesize and process information while listening 3) psychological mechanisms should be developed; 4) apperception should be activated before listening; 5) students should be able to share their "projection" of the audiobook.